2017
DOI: 10.1055/s-0043-110863
|View full text |Cite
|
Sign up to set email alerts
|

Duty Rosters and Workloads of Obstetricians in Germany: Results of a Germany-wide Survey

Abstract: The results of this study show that the conditions of work, the working times, and the organization of working times in obstetric departments are in need of improvement. Recording the actual times worked together with an analysis of the activities performed during working times and while on standby would increase the level of transparency for employers and employees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
2
2
0
2
Order By: Relevance
“…Hence, studies including more professionals are needed to support these preliminary results. However, the number of participants in this study was in concordance with other studies in this field [ 25 , 41 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, studies including more professionals are needed to support these preliminary results. However, the number of participants in this study was in concordance with other studies in this field [ 25 , 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…These results are in accordance with those of other previous studies, showing that doctors are satisfied with their profession in general [ 24 ]. However, this is usually affected by organizational issues both in Germany [ 25 ] and other countries worldwide [ 26 ]. Recent studies have indicated that the workload of most doctors in Germany increased within the last couple of years [ 27 ] and that most health care professionals are aware of the health risks associated with night shifts, such as sleeping problems and hypertension [ 28 - 30 ], and this result is in accordance with the responses in our survey.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite the limited use of telemedicine so far and a prevalence of sleeping disorders of around 40% among our study population, the overall job satisfaction was highirrespective of age and the number of night shifts per month. This is in accordance with other previous studies that have shown a satisfaction among doctors in general with their profession [24] but mostly hindered by organizational issues, both in Germany [25] and internationally [26]. Recent studies indicate that the workload increased for the vast majority of doctors in Germany in the last couple of years [27] and that most health care professionals are aware of the health risks associated with night shifts such as sleeping problems and hypertension [28][29] [30] in accordance to the responses in our survey.…”
Section: Discussionsupporting
confidence: 93%
“…Unsere Rückmeldungen stützen den zuletzt 2019 erhobenen Trend, dass die Arbeitsrahmenbedingungen als unzureichend und die Arbeit selbst als übermäßige Belastung empfunden werden. Auch die wöchentliche Arbeitszeit verbleibt hoch, wie bereits 2015 durch das junge Forum festgestellt wurde [ 12 , 19 ]. Insbesondere bei der tatsächlichen Wochenstundenzahl wünschen sich die Kolleginnen und Kollegen eine Veränderung.…”
Section: Diskussionunclassified
“…Darüber hinaus nimmt die Berücksichtigung unterschiedlicher Generationencluster im Gesundheitswesen an Fahrt auf [ 3 – 6 ], und die Sensibilisierung gegenüber den Anforderungen und Bedürfnissen der jungen Ärztegeneration rückt fächerübergreifend in den Vordergrund [ 7 – 11 ]. Zunehmend erreicht die Auseinandersetzung mit der nachfolgenden Generation auch das Fachgebiet Frauenheilkunde und Geburtshilfe [ 10 , 12 15 ]. Dabei bedarf es stetiger Anstrengungen, um die Generationencluster in diesem Fachgebiet weiterhin zu charakterisieren, Arbeitsbedingungen und -belastung inklusive deren Auswirkungen auf den ärztlichen Nachwuchs zu eruieren, Weiterbildung und Nachwuchsförderung zu optimieren und praxistaugliche Lösungen in den Klinikalltag zu implementieren.…”
Section: Introductionunclassified